1997
DOI: 10.1007/s005200050066
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of infections in the adult medical intensive care unit of a cancer hospital

Abstract: A prospective collection of positive antimicrobial cultures was performed over 12 consecutive months in the medical intensive care unit of a cancer hospital. In all, 144 infections and 163 pathogens were documented during 87 of the 528 admissions. Lung, urinary, ENT (ear, nose and throat) infections and bacteraemia were the most frequently documented. Staphylococcus species, Streptococcus species, Escherichia coli, Klebsiella species and Pseudomonas species were the most common pathogens. Gram-positive strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…Informed consent was obtained from all patients. Pneumonia, including nosocomial pneumonia, is one of the main complications occurring in lung cancer patients due to defects in the clearance system in sites peripheral to the bronchial obstruction, or stenosis caused by cancer therapy as well as cancer itself and broad-spectrum antibiotics usage [7][8][9][10][11][12][13][14]. The role of anaerobes in the pathogenesis of pneumonia in hospitalized patients, especially in critically or chronically ill patients, is still controversial [4,15,16].…”
mentioning
confidence: 99%
“…Informed consent was obtained from all patients. Pneumonia, including nosocomial pneumonia, is one of the main complications occurring in lung cancer patients due to defects in the clearance system in sites peripheral to the bronchial obstruction, or stenosis caused by cancer therapy as well as cancer itself and broad-spectrum antibiotics usage [7][8][9][10][11][12][13][14]. The role of anaerobes in the pathogenesis of pneumonia in hospitalized patients, especially in critically or chronically ill patients, is still controversial [4,15,16].…”
mentioning
confidence: 99%
“…In particular, patients with malignancy have a high risk of MRSA infection. Cancer chemotherapy may induce an immunosuppressed condition; radiotherapy often elicits local inflammation, especially mucitis; and surgery breaks local barriers against pathogens and could cause MRSA wound infection [8,9]. Of the 318 consecutive patients with head and neck cancers in the present study, about 14% were positive for MRSA.…”
Section: Discussionmentioning
confidence: 97%
“…The risk factors for having the MDR include the previous chemotherapy and prior admission [10] . Indeed, it is reported that E. coli is one of the most common pathogen identified in medical oncology hospital [11] . However, if the good infectious control is implemented, outbreak can be successfully controlled [11] .…”
Section: E Coli Outbreak Among the Cancerous Patientsmentioning
confidence: 99%